A Study on the Contributing Factors of Major Landslides in Malaysia - Danish Kazmi; Sadaf Qasim; I.S.H Harahap; Syed Baharom; Muhammad Imran; Sadia Moin (Civil Engineering Journal, 2016)
Landslide is one of the most prominent geo-hazard that accounts for colossal losses every year. The contributing factors of landslides in Malaysia are reasonably different from rest of the world. According to a study, the most dominant factor that catalysis the slope failure in many countries of the world is geological conditions. However, in case of Malaysia; most of the landslides occur as a consequence of flawed design, improper construction and non-maintenance of slopes which correlates with the human errors. The statistics of Malaysia shows that highest number of landslides took place in 1996 with 71 cases which is followed by 68 cases in 1995. According to the findings of Highland Towers (1993) landslide, the main causes of failure were inaccuracies in design, poor supervision during the construction and inadequate drainage system. Similarly, in case of Taman Hillview and Bukit Antarabangsa landslide, it has been revealed that improper design practices and poor drainage system supplemented with prolonged rain were the significant causes of the cataclysm. Therefore, based on the investigations on retrospective landslides, this study proposes to incorporate Human Reliability Assessment technique as a part of working strategy for slopes along with strong adherence to the design guidelines in order to minimize the likelihood of landslides.